2016
DOI: 10.1002/chem.201601506
|View full text |Cite
|
Sign up to set email alerts
|

An Unprecedented Two‐Fold Nested Super‐Polyrotaxane: Sulfate‐Directed Hierarchical Polythreading Assembly of Uranyl Polyrotaxane Moieties

Abstract: The hierarchical assembly of well-organized submoieties could lead to more complicated superstructures with intriguing properties. We describe herein an unprecedented polyrotaxane polythreading framework containing a two-fold nested super-polyrotaxane substructure, which was synthesized through a uranyl-directed hierarchical polythreading assembly of one-dimensional polyrotaxane chains and two-dimensional polyrotaxane networks. This special assembly mode actually affords a new way of supramolecular chemistry i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 81 publications
2
5
0
Order By: Relevance
“…For the MORFs utilizing cucurbituril-based pseudorotaxane/rotaxane linkers, only a handful of MORFs of this type have been reported. , Besides porosity or dynamics for rotaxane-based MOFs, high-order assembly between different well-organized metal–organic rotaxane submoieties and the resulting complicated topology should also be taken into account, as another interesting issue concerning the supramolecular behavior of MORFs is high-order assembly between different well-organized metal–organic rotaxane submoieties just like the assembly of supercoil structure of DNA in biological systems. Whang et al and Liang et al have respectively reported different structural patterns with polycatenating through either inclined interweaving or parallel interpenetration. , In fact, we described another polythreading model of uranyl-containing MORFs, which was based on another assembly mode, that is polythreading . The high-order assembly shown in the above cases verifies the feasibility employing cucurbituril-bearing supramolecular ligands to conduct the high-order assembly of MORFs.…”
Section: Resultssupporting
confidence: 68%
See 2 more Smart Citations
“…For the MORFs utilizing cucurbituril-based pseudorotaxane/rotaxane linkers, only a handful of MORFs of this type have been reported. , Besides porosity or dynamics for rotaxane-based MOFs, high-order assembly between different well-organized metal–organic rotaxane submoieties and the resulting complicated topology should also be taken into account, as another interesting issue concerning the supramolecular behavior of MORFs is high-order assembly between different well-organized metal–organic rotaxane submoieties just like the assembly of supercoil structure of DNA in biological systems. Whang et al and Liang et al have respectively reported different structural patterns with polycatenating through either inclined interweaving or parallel interpenetration. , In fact, we described another polythreading model of uranyl-containing MORFs, which was based on another assembly mode, that is polythreading . The high-order assembly shown in the above cases verifies the feasibility employing cucurbituril-bearing supramolecular ligands to conduct the high-order assembly of MORFs.…”
Section: Resultssupporting
confidence: 68%
“…46,47 In fact, we described another polythreading model of uranyl-containing MORFs, which was based on another assembly mode, that is polythreading. 48 The high-order assembly shown in the above cases verifies the feasibility employing cucurbituril-bearing supramolecular ligands to conduct the high-order assembly of MORFs. Further exploration on new MORFs with high-order assembly will help us to study and understand the supramolecular behavior and weak interactions of pseudorotaxane or rotaxane submoieties during the process of assembly.…”
Section: ■ Experimental Sectionsupporting
confidence: 59%
See 1 more Smart Citation
“…To date, there have been numerous reports on the use of MIMs (almost exclusively using pseudorotaxane precursors) as linkers in coordination polymers to create interesting crystalline lattices, ,, but few of these materials employ actinides as metal nodes. To this end, we have recently reported a series of interesting 1D, 2D, and 3D coordination polymers with rotaxane linkers and uranyl nodes, which encourage us to pursue more well-designed actinide polyrotaxanes with intriguing topologies and potential functions through the utilization of new synthesis strategies and methods.…”
Section: Introductionmentioning
confidence: 99%
“…As a new synthesis methodology, a mixed-ligand system provides an alternative route to tune the structure and properties of metal–organic compounds by introducing a second functional organic or inorganic ligand as the coligand. , In our previous work, a similar strategy has been also used to assemble uranyl-organic rotaxane compounds with an inorganic sulfate ion involved. However, a combination of a pseudorotaxane ligand and simple organic ligands have never been used in uranyl polyrotaxanes. Oxalate, which has been intensively studied for their potential application in actinide separation reprocessing of spent nuclear fuel, could be a versatile ligand with small steric hindrance and different coordination possibilities .…”
Section: Introductionmentioning
confidence: 99%